A Igreja Universal do Reino de Deus no "jogo do poder": a aliança com o Partido dos Trabalhadores nas eleições presidenciais de 2002 - Cruz, Marcelo Pereira da (2009)
Among all kinds of societies, religion and the power of the State outline alliances that have brought benefits and tensions. Religion was one of the first ones that emerged in the middle of a society, providing union around a divinity. Along history, kings, emperors, dictators and, according to a modern conception of the word, politicians saw religion as a great strength to help them in the process of leading the society through the development of doctrines and rules. Those relations changed the religious and political specialists into important agents inside societies due to the control of the relations among people which they influence. In Contemporary Brazil, the participation of religion in politics is a fact that has been repeated with Igreja Universal do Reino de Deus (IURD), which has gained prominence in the politics field due to its spectacular development and to the transference of its religious capital, through its theology, practices and speeches. Igreja Universal fits a third wave of Pentecostal churches which were developed in Brazil by the seventies, however, their practices and theology which were adapted to the social context where it is inserted, made it become a phenomenon which transcended the religious frontiers. The place conquered by IURD in the religious, social, media, business and political fields, worked as inspiration for other religious denominations, that followed their steps. The success of IURD, particularly, in the politics field was reached through bold strategies, which had begun with their candidate‟s choice and later with the liaison to PL (Partido Liberal), a right party, whose principles and ideologies fit perfectly to IURD ideals and beliefs. However, the church had to overcome a difficult moment in the nineties because of internal scandals involving their main leaders and mistakes made by the summit of the church by supporting, for example, Fernando Collor de Mello in the presidential elections of 1989 and the disappointment with Fernando Henrique Cardoso government. Those events ended up in a change of attitude towards Partido dos Trabalhadores, their old left issue and formed a victorious union between IURD/PL and PT, in the presidential elections of 2002, which resulted in the victory of Luiz Inácio Lula da Silva and in the reinforcement of Igreja Universal do Reino de Deus